Frictionless fruit. (Economist, 2014)
The article considers the 2014 introduction by high technology industries firm Apple Inc. of two operating systems, the OS X Yosemite for microcomputers and the iOS 8 for mobile computers. The ability of the operating systems to provide integration of operations on both forms of computers is examined. Swift, a programming language introduced by Apple, is considered in relationship to its plan to allow mobile device application developers more autonomy in designing for Apple products.